Occurrence of false positivity in a fourth generation (Ag/Ab) HIV screening assay: horns of a dilemma - Roy, Partha; Kapoor, Ruchi; Rawat, Priya; Aggarwal, Monika; Gaur, Ravi; Anand, Mrunalini; Saharia, Pallav (International Journal of Research in Medical Sciences, 2018)
Background: Universal screening for HIV with Ag/Ab combo assays has reduced the window period significantly due to its high sensitivity. However, occurrence of false positives is common and in a country like India, it may lead to social distress and loss of livelihood. We wanted to ascertain the occurrence of false positives in our laboratory. Methods: There were 21817 samples analysed retrospectively from Jan 2015 to Jul 2017 (31 months). Architect HIV Ag/Ab Combo (Abbott Laboratories, Abbott Park, IL) was used as the first test. Repeatedly reactive samples with a signal to cutoff (S/CO) ratio greater than or equal to 1.00 was considered reactive. Strategy III (3 test algorithm) of NACO guidelines was followed uniformly. Results: In this study, 147 samples tested reactive (0.67%) and 40 samples tested false positive (repeatedly reactive; 0.18%). 6 samples were indeterminate (0.027%). Overall, the sensitivity of the Architect HIV Ag/Ab Combo was 100%, the specificity varied between 99.74% and 99.91%. The PPV from June 2016 to July 2017 was 68.63% (32 false positives). The S/CO values of 72.8% (117/147) reactive samples ranged between 201- 800, whereas 72% (29/40) of false positive samples, the S/CO values ranged between 1.0-2.0. The specificity of the test improved to 99.98% when S/CO value was adjusted at 2 and 100% when adjusted at 5. Similarly, the PPV too improved to 93.04% and 98.66% at S/CO values of 2 and 5 respectively. Conclusions: Further studies are needed to ascertain the optimal or ‘grey-zone’ S/CO values for India to minimise the false positive results and avoid further supplemental tests routinely.